Improving oral presentation skills for radiology residents through clinical session meetings in the virtual world Second Life - Pino-Postigo, Alberto; Domínguez-Pinos, Dolores; Lorenzo Álvarez, Rocío; Pavía-Molina, José; Ruiz-Gómez, Miguel José; Sendra-Portero, Francisco (MDPI, 2023)
Background: The objective of this study was to conduct a clinical session meeting in the virtual world of Second Life to improve the oral presentation skills of radiology residents and to assess the perception of the attendees. Methods: A clinical session meeting (10 two-hour sessions over four weeks), where participants presented their own clinical sessions, followed by a turn of interventions by the attendees, was designed and carried out. Attendees were asked to complete an evaluation questionnaire. Descriptive statistics were performed. Results: Twenty-eight radiology residents attended the meeting, and 23 (81.2%) completed the evaluation questionnaire; 95.7–100% of them agreed that the virtual environment was attractive and suitable for holding the meeting and that the content was appropriate for their training as residents. They rated with ≥8.9 points (from 1 to 10) different aspects of the experience, highlighting the role of teachers (9.7 ± 0.6) and the usefulness of their training (9.4 ± 0.9). Conclusions: Second Life can be used effectively to train oral communication skills in public, in an environment perceived as attractive and suitable for learning, through an experience described by the attendees as interesting and useful, highlighting the advantages of social contact with their peers
Keywords: Radiología -- Formación profesional; Internet en la enseñanza; Charlas por Internet; Radiology education; Virtual worlds; Residents; Oral presentation; Clinical sessions